Specification for low-voltage switchgear and controlgear assemblies. Particular requirements for assemblies intended to be installed outdoors in public places. Cable distribution cabinets (CDCs) for power distribution in networks Part 5, (15th March 2000) - British Standards Institution,
No abstract available